(untitled) (Anclajes, 2025)
Within the framework of a general and broader research about how the gauchesca influenced centralizing the figure of the gaucho in national culture, it focuses on Santos Vega, by Hilario Ascasubi from three aspects, namely: the gauchesca poetry as an aesthetic form that establishes dissent and consensus around how to understand the nation’s people; the fictionalization of the rest of the plebs in a differential manner with respect to the gaucho; and, finally, a temporal look that includes the colonial. Santos Vega, by Hilario Ascasubi, constitutes a decisive text to understand, from literature, that dynamic that made the gaucho the outstanding commoner of the Argentine Nation.